Fasciatherapy and Reflexology compared to Hypnosis and Music Therapy in Daily Stress Management - Payrau, MD, MT, Bernard; Quere, MSc, PT, MT, Nadine; Breton, MSc, Elisabeth; Payrau, MD, Christine (International Journal of Therapeutic Massage & Bodywork, 2017)
Background: Patients suffering from stress symptoms due to every-day life who are looking for a nonpharmacological response to their relief expectation are many. Furthermore, early reckoning of the day-to-day stress which may lead to clinical diagnosis is the best way of preventing the stress-related diseases. Among the many alternative medicinal options, there is little evidence that fasciatherapy (Fs) and reflexology (Rf) are effective in this field. Purpose: assess incidence of fasciatherapy Danis Bois Method (DBM) and of reflexology on patients’ stress level in everyday-life, and provide a more informed choice among the numerous mind and body techniques by comparing them with hypnosis (Hp) and music therapy (Mt). Settings: Specialized Complementary and Alternative Medicine (CAM) centres for outpatients. Participants: 308 individuals (average age = 50.53 SD 14.37, 93 males, 215 females) going to the centres for health care, but free from serious diseases and not heavily medicated respecting the inclusion criteria and providing valid forms. Research Design: Four armed, non-randomized observational pragmatic trial with pretest–posttest repeated measures, on separate samples of natural groups. Intervention: According to the centre participants where they used to be treated, they were exposed to a single semi-standardized session of a technique of their choice: Fs, Rf, Hp, Mt. Volunteers had a controlled non-intervention resting (Rt) session. Main Outcome Measures: Mean STAI-Y assessing anxiety as reflecting the stress level: MANCOVA and ANCOVA performed with Tukey’s HSD. Results: MANCOVA indicates a significant reduction of anxiety (p < .01) in each condition, resting included. ANCOVA performance adjusting on stress level in T0 (41.73) and on the mean sumscore of the trait (44.89), Fs (-13.92), Rf (-15.92), and Hp (-15.88) were equally effective on the stress level decrease. Mt (-10.0) and Rt (-6.38) showed the same level of effectiveness. Conclusions: The results suggest fasciatherapy DBM, hypnosis, and reflexology could be used as non-pharmacological and safe interventions in stress management. Though showing a lesser efficiency, music therapy could be useful in different circumstances.